Penerapan Model Round Robin Brainstorming dalam Meningkatkan Kerjasama Tim - Amallah Nur Amanah; Ismail Hidayat; Subiyati Subiyati; Murtiningsih Murtiningsih; Heru Maryatun; Imam Rofingi (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to describe the steps, advantages, and disadvantages of applying the Round Robin Brainstorming learning model in PPKn (Civics Education) at MTs N 1 Klaten, MTs N 5 Karanganyar, and MAN Kebumen. This research uses a qualitative approach. The informants being. Data collection techniques include interviews, observations, and documentation. The results of this study are: 1) The steps of the Round Robin Brainstorming model include students forming groups, with each member taking turns in a clockwise direction to respond to questions. If necessary, students can take on roles as note-takers or rule enforcers. It is explained to the students whether they will take turns once in sequence or several times, and one student is asked to start the activity by offering an idea or response verbally; 2) The advantages of the Round Robin Brainstorming model include its effectiveness in eliciting many ideas, as it requires all students to participate. It can solve participation issues, ensuring equal participation, and can enhance student interaction, fostering cooperation and improving learning outcomes; 3) The disadvantages of the Round Robin Brainstorming model include the need for specific skills that students may not have learned before, the possibility of group discussions being dominated by a few outspoken students, and students often being reluctant to express their opinions during group discussions. The conclusion of this study is that the Round Robin Brainstorming model can be applied in the learning process to enhance teamwork during lessons and is effective in improving learning outcomes.